The Efforts of Improving Motivation and Learning Outcomes Through The Power Of Two Type in the History Subject at Grade X Iis 3 in Sman 7 Solok Selatan - Yondri Fernando; Siti Fatimah (Postgraduate School, Universitas Negeri Padang, 2020)
The active learning strategy of the Power of Two type means the active learning strategy which in its application uses the strength learning techniques of two people to increase motivation and learning outcomes. Based on this, this research aims to determine the efforts to improve motivation and learning outcomes through the The Power of Two type in the History Subject at grade X IIS 3 in SMAN 7 Solok Selatan. The research method used was a classroom action research. The research was conducted in SMAN 7 Solok Selatan in the second semester of the 2018/2019 academic year. The research subjects were 24 students of grade X IIS 3. The researchwas conducted in 3 cycles: planning, action, observation and reflection phase. The data analysis technique consisted of a descriptive and qualitative analysis. The results of the research were as follows (1) The use of the The Power of Two type could increase the motivation of students of grade XI IIS 3 in SMAN 7 Solok Selatan; in the first cycle the motivation for the medium category was 49.72%, increasing to 58.76%; cycle II and cycle III were included in the high category with a percentage of 69.23% and (2) The use of the The Power of Two type could improve student learning outcomes of grade XI IIS 3 in SMAN 7 Solok Selatan. In the first cycle, the mean score of the student learning outcomes was unsatisfactory: 64.58 with a percentage of completeness of 12.5%. Then, the second cycle increased by an mean score of 71.67 with a percentage of completeness of 20.83%% and in the third cycle of 78.75 with a percentage of completeness 87.5%.